Arthroscopic Fixation of a Posterior Cruciate Ligament Avulsion Fracture: A Case Report - I Made Wahyu Adi Putrawan; I Komang Mahendra Laksana Mendra (The International Journal of Medical Science and Health Research, 2026)
Introduction: Avulsion fractures of the posterior cruciate ligament (PCL) are relatively uncommon injuries, particularly in the adolescent population. These injuries involve detachment of the ligament from its tibial insertion and may result in persistent posterior knee instability if not properly managed. Accurate diagnosis and appropriate fixation are essential to restore normal knee kinematics and prevent long-term complications. Case Illustration: This report presents the case of a 16-year-old female patient with a 3-month history of left knee pain and instability following a fall during training. Clinical examination revealed positive posterior drawer and valgus stress tests. Magnetic Resonance Imaging (MRI) confirmed a displaced tibial avulsion fracture of the PCL (Meyers-McKeever Type III) and a concomitant full-thickness MCL tear. The patient underwent a single-stage procedure: arthroscopic suspensory button fixation for the PCL avulsion and an anatomic reconstruction of the MCL. Discussion: Surgical management is superior to non-operative treatment for displaced PCL avulsions, citing improved union rates and better objective stability (Gopinatth et al., 2023). The rationale for selecting an arthroscopic suspensory fixation technique (Kan et al., 2020) over traditional open or arthroscopic suture methods is discussed, highlighting its minimally invasive nature, robust fixation, and avoidance of complications associated with other techniques (Hu et al., 2025). Conclusion: Arthroscopic suspensory fixation represents an effective and reliable treatment option for displaced PCL tibial avulsion fractures in adolescents. This technique enables stable fixation, supports early rehabilitation, and contributes to satisfactory restoration of knee stability, even in chronic cases.